On Certain Subclasses of Meromorphic Functions Associated with Noor Integral Operator - Abdusalam.R. Ahmed; Milad E. Drbuk; Enas. A. Almontasri (Journal of Libyan Academy Bani Walid, 2025)
This paper investigates certain subclasses of meromorphic functions associated with the Noor integral operator. The study focuses on exploring the properties of subordination and convolution for these subclasses, through precise definitions and their connection to the Noor operator. The work is supported by a set of theorems and complementary results that strengthen the theoretical framework and clarify how these subclasses are related to fundamental properties in the theory of analytic and meromorphic functions. The paper also includes preliminary lemmas that form the foundation for proving the main results, along with several corollaries that illustrate specific cases and applications of the studied subclasses. The significance of this research lies in its contribution to the field of meromorphic function theory by linking it with modern integral operators, thereby opening new avenues for the study of related mathematical structures and broader applications in complex analysis.